Onthophagus acernorus (Coleoptera: Scarabaeidae: Scarabaeinae: Onthophagini), a new dung beetle species from Jalisco, Mexico - Moctezuma, Victor; Hernández, Benjamín; Sánchez-Huerta, José Luis; Navarrete-Heredia, José Luis; Martínez-Rodríguez, Pablo Antonio (Zootaxa, 2021)
The Onthophagus chevrolati Harold, 1869 (Coleoptera: Scarabaeidae: Scarabaeinae: Onthophagini) species complex was recently studied, and a majority of its species were newly described or redescribed (see Moctezuma & Halffter 2020). Onthophagus viridichevrolati Moctezuma & Halffter, 2020 was the only species within the O. chevrolati species complex recognized to occur in the Mexican state of Jalisco (Moctezuma & Halffter 2020). Recently, new material belonging to the O. chevrolati species complex was collected from the maple (Acer; Sapindaceae) forests of Talpa de Allende, Jalisco, Mexico. The examination of these specimens showed that they are morphologically similar to O. chevrolati Harold, 1869 and belong to an undescribed species. In this study, we provide photographs of the habitus (male and female) and male genitalia of O. acernorus   new species; an identification key to separate it from O. chevrolati, and an updated distribution map of the O. chevrolati species complex.